Mechanical Properties and Formaldehyde Emission of Rubberwood Particleboard Using Emulsified Methylene Diphenyl Diisocyanate (EMDI) Binder at Different Press Factor Continuous Press - Y. Ab Hafidz, M.; F. Mohd2, A.; Zulkifli, M. (International Journal of Engineering and Technology, 2019)
Rubberwood particleboard with low formaldehyde emission is a must in wood based paneling industry especially for export market such as in Japan, Korean, European countries and North America Region. Avoiding of urea formaldehyde binder and substitute it with emulsion isocyanate resin is an alternative in particleboard production. However, the low tackiness and sticking to steel belt during transferring and pressing in actual particleboard production contributes to surface defects as well as variation in mechanical properties of the final product. The results revealed that a correlation speed and press factor is necessary in order to improve mechanical properties and to keep the physical performance of boards within a limited range of values. Various speeds of press factors were studied at 15.0, 14.5, 14.0, 13.5 sec/mm to study the effect to the bending, internal bonding, screw withdrawal, surface soundness, thickness swelling, moisture content properties and formaldehyde emission of particleboard. At higher production speed (lower press factor), bending, internal bonding, MOE and edge screw withdrawals properties of particleboard was decrease by 3% to 13%. Thickness swelling and moisture content were increased in final particleboard production. Emission of formaldehyde was below than 0.15 mg/L (JIS A 1460) at all speeds of press factor which is extremely low.Â Â Â